Educação patrimonial: um olhar sobre as Igrejas de Penedo – AL e a distinção social no Século XVIII - Macêdo, Emanuelle Socorro Goes de (2022)
The present work had as objective the construction of the didactic script called Small Manual of Heritage Education: a direction for the use of the Penedense heritage, which aims to prepare the teacher for an effective heritage education. For this work, a literature review was used as a methodology, having as main authors Bittencourt, Zarbato, Almir Oliveira, Ernani Méro, Fabiane Alves, Paulo Freire and Hall. The script enables the application of the methodology of heritage education in the teaching of history as a way to develop the epistemological curiosity necessary for the implementation of autonomous knowledge of a critical-libertarian nature, focusing on ethnic-racial issues of the 18th century, passing through Penedo's religious history as a preponderant factor for the racial distinction that occurred in the eighteenth century.